Does the Business Model Increase Bank Stability? - Nguyen, Loan Thi Nguyet; Tran, Phuong Thi Lan; Trinh, Nguyet Thi Minh; Le, Anh Quynh (Financial Risk and Management Reviews, 2022)
Research on risk or sustainability in the banking system does play an important role in the banking industry, where competitiveness increases unceasingly. Simultaneously, the trend of diversifying banks’ business models is becoming more popular. Thus, this paper attempts to investigate the impact of business model diversification on bank risk and stability. The proxy of business models includes (1)Non-net interest income; (2) trading income. The paper applied Generalized Least Squares (GLS) to conduct empirical research on 18 joint-stock commercial banks listed on the Vietnam Stock Exchange from 2010 to 2019 (The GLS with panel data). The results indicated the negative impact of non-net-interest income on bank stability. Trading in foreign exchange, gold has no meaning for bank risk. The study offers some theoretical and practical implications for banks to control better risks based on new empirical findings. Especially, the diversification of business models is ineffective, and banks need more suitable solutions.